(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
India is considered as a largest democratic country in the world but the activities of terrorismhas shaken the guards of democracy and freedom. Availability of modern technologies and weapons hasadded fuel to the activities of terrorism as weapons are easily available to the terrorists groups.Therefore for a world “war itself is a terrorism” because world needs to fight with the activities ofterrorism to remove it from roots. This Article highlights the major causes and discuss in detail theimpact of terrorism as it is a matter of prime concern to sustain democracy and law for peace as well asfor the survival of human humanity.